ما بعد الانتقال - صحراوي, فايزة (جامعة الوادي University of Eloued, 2019)
تدرس هذه الورقة تحديات إصلاح القطاع الأمني في تونس ما بعد الانتقال، البلد العربي الأول الذي أشعل فتيل الانتفاضات الشعبية العربية سنة 2010، محاولة إبراز مجموع المشكلات والمعضلات التي يطرحها هذا التعثر في العملية الإصلاحية على مسار الانتقال الديمقراطي في البلاد. فبالنظر إلى الدور الكبير الذي لعبته بعض الأجهزة الأمنية في دعم نظام بن علي الاستبدادي، تلقي هذه الورقة الضوء على الخصائص العامة للجهات الفاعلة في قطاع الأمن التونسي خلال عهد بن علي، لتنتقل لاحقا إلى مناقشة مدى فعالية ومحدودية الإصلاحات الأمنية المنجزة في فترة ما بعد الانتقال، مفسرة رهانات وآفاق إصلاح قطاع الأمن في تونس من خلال النظر في المتطلبات والمسارات العملية المتعلقة بتحسين أداء القطاع الأمني وإعادة هيكلته نحو مزيد من الشفافية والمساءلة والرقابة المدنية الديمقراطية بشكل يعكس حدوث تغيير حقيقي وإصلاح مؤكد في الدولة التونسية. This paper examines the challenges of security sector reform in post-transition Tunisia, the first Arab country have ignited the Arab popular uprisings in 2010, in an attempt to highlight the set of problems and dilemmas posed by this stumbling in the reform process on the path of democratic transition in the country. So in view of the great role played by some security agencies in supporting the authoritarian Ben Ali' regime, this paper sheds light on the general characteristics of the actors in the Tunisian security sector during the Ben Ali era. It then moves on to discuss the effectiveness and limitations of the post-transition security reforms, to explaining the stakes and prospects of security sector reform in Tunisia by considering the viable requirements and paths to improve security sector performance and restructuring it towards more of accountability, transparency and democratic civil control in a way that reflects a real change and a definite reform in Tunisia.
تحديات إصلاح القطاع الأمني في تونس
Keywords: ما بعد الانتقال ; الإصلاح ; قطاع الأمن ; التحديات ; تونس